2020
DOI: 10.1038/s41438-020-00379-w
|View full text |Cite
|
Sign up to set email alerts
|

Color-related chlorophyll and carotenoid concentrations of Chinese kale can be altered through CRISPR/Cas9 targeted editing of the carotenoid isomerase gene BoaCRTISO

Abstract: The carotenoid isomerase gene (BoaCRTISO) of Chinese kale was targeted and edited using the CRISPR/Cas9 system in the present study. The results showed a high mutation rate (81.25%), and 13 crtiso mutants were obtained. Only two types of mutations, insertions and replacements, were found. Both the total and individual carotenoid and chlorophyll concentrations of the biallelic and homozygous mutants were reduced, and the total levels declined by 11.89–36.33%. The color of the biallelic and homozygous mutants ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Moreover, we found three ISO genes ( BnZ-ISOa , BnZ-ISOa and BnCrtISOa ) were significantly downregulated in WP vs. ZS11 petals at S1, which may be related to the reduced total lutein and zeaxanthin contents in the white-flowered line. In the crtiso mutants of Chinese kale, the carotenoid isomerase gene ( BoaCRTISO ) was targeted and edited using the CRISPR/Cas9 system, the expression levels of CRTISO and most carotenoid and chlorophyll biosynthesis-related genes were notably lower than in the WT plants, in addition, both the total and individual carotenoid and chlorophyll concentrations were reduced, and the total levels declined by 11.89–36.33% (Sun et al 2020 ). Most importantly, BnNCED4b was dramatically upregulated in WP petals and showed almost no expression in ZS11 petals, suggesting that this gene plays a key role in turning WP petals from pale yellow to white.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found three ISO genes ( BnZ-ISOa , BnZ-ISOa and BnCrtISOa ) were significantly downregulated in WP vs. ZS11 petals at S1, which may be related to the reduced total lutein and zeaxanthin contents in the white-flowered line. In the crtiso mutants of Chinese kale, the carotenoid isomerase gene ( BoaCRTISO ) was targeted and edited using the CRISPR/Cas9 system, the expression levels of CRTISO and most carotenoid and chlorophyll biosynthesis-related genes were notably lower than in the WT plants, in addition, both the total and individual carotenoid and chlorophyll concentrations were reduced, and the total levels declined by 11.89–36.33% (Sun et al 2020 ). Most importantly, BnNCED4b was dramatically upregulated in WP petals and showed almost no expression in ZS11 petals, suggesting that this gene plays a key role in turning WP petals from pale yellow to white.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the chlorophyll content showed a higher decrease than the carotenoid content, and the decrease was greater for chlorophyll b content than chlorophyll a content. Previous studies have shown that chlorophyll is responsible for the green pigmentation in plants, and the presence of carotenoids affects leaf color (Wu et al, 2018 ; Sun et al, 2020 ). We speculated that this significant change in the photosynthetic pigment was the direct cause of the pale green phenotype in pem1 and pem2 .…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that the phenotypes of leaves and other organs are expressed differently according to species after CRTISO is silenced. Besides, after the BoaCRTISO gene was target-edited in Chinese kale, the plant showed a distinct yellow color, although the gene expression level was similar to that of the VIGS plants (Sun et al, 2020). This shows that stable plant transformation can make plants show a more obvious phenotype than transient VIGS technology.…”
Section: Discussionmentioning
confidence: 96%